Increment of Maternal Mortality Among Admissions for Childbirth in Low-risk Pregnant Women in Brazil: Effect of COVID-19 Pandemic? - Bruna Depieri Michels; Daniela Ferreira D'Agostini Marin; Betine Pinto Moehlecke Iser (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2022)
Abstract Objective To assess the possible impact of the COVID-19 pandemic on maternal mortality among admissions for childbirth in 2020 in relation of the last 10 years. Methods An ecological study with pregnant women who underwent hospital births at the Brazilian unified public health service (SUS, in the Portuguese acronym) in Brazil from 2010 to 2020. The mortality among admissions for childbirth was obtained based on the number of admissions for childbirth with reported death as outcome divided by the total number of admissions. The underlying gestational risk and route of delivery were considered based on the national surveillance system. The average mortality for the period between 2010 and 2019 (baseline) was compared with the rate of deaths in 2020 (1st pandemic year); the rate ratio was interpreted as the risk of death in 2020 in relation to the average of the previous period (RR), with 95% confidence intervals (CIs). Results In 2020, the 1st year of the COVID-19 pandemic, 1,821,775 pregnant women were hospitalized for childbirth and 651 deaths were reported, which represents 8.7% of the total hospitalizations and 11.3% of maternal deaths between 2010 and 2020. There was an increase in maternal mortality after births in 2020 compared with the average for the period between 2010 and 2019, specially in low-risk pregnancies, both in vaginal (RR = 1.60; 95%CI:1.39-1.85) and cesarean births (RR = 1.18; 95%CI:1.04-1.34). Conclusion Maternal mortality among admissions for childbirth according to SUS data increased in 2020 compared with the average between 2010 and 2019, with an increment of 40% in low-risk pregnancies. The increase was of 18% after cesarean section and of 60% after vaginal delivery.